Inherent Constraints and Creative Possibilities : Employee Participation in Kenya - McCourt, Willy; Brunt, Carol (Taylor and Francis, 2013)
We present findings from a study of employee participation in seven International NGOs (INGOs) operating in Kenya. The inherent constraints of hierarchy and the need to accommodate a range of stakeholder interests imposed a strict ceiling on the degree of participation even in this propitious environment. Being headquartered in a liberal market economy, the low salience of trade unions among Kenyan employees and/or individual management styles within the INGOs meant that some of the agencies fell short even of that ceiling. Contrary to the normative aspirations of both the HR and international development literatures, our study suggests that the co-determination and employee control styles of participation are undesirable and unrealistic goals. On the other hand, a consultation style of participation was appropriate to the seven INGOs, and may also be in other sectors and countries.